Faktor Resiko yang berhubungan dengan Kejadian Low Back Pain (LBP) Pada Pembatik - Faridah, Faridah; Hadi, Putra (Jurnal Akademika Baiturrahim Jambi, 2024)
Complaints batik is a worker who has a limited work space with a static work position for a certain time. Inappropriate and non-ergonomic work positions that are repeated in long periods of [i]confinement can result in work-related illnesses such as low back. As many as 100% of cases of back pain not caused by organic abnormalities, but by mistakes in body position in work. The purpose of this research is to know the factors related to low back pain with age, length of work, work period, work position and nutritional status in the complaints batik.The type of research is observational analytic with cross sectional study design. The population is a permanent employee carrier with a total of 30 people and sampling techniques using exhaustive sampling. The low back pain event was supplemented by the Oswestry Disability Index (ODI) questionnaire, the work position measured by Rapid Entire Body Assessment (REBA) and nutritional status was measured by Microtoice and Weighing Scales..The results showed that as many as 63% of complaints batik low back pain events. Cross tabulation results show that there is correlation between low back pain with age (pvalue = pvalue=0.029<0.05), length of work (pvalue=0.028<0.05), working period (pvalue=0.029<0.05), whereas no correlation working position (pvalue= (pvalue=0.781 >0.05) and nutritional status (pvalue = 0.089 <0.05).Based on the above results, it is advisable for the operator to minimize non- stop work, stretching interrupted at work time and resting time utilization